Comparative RNA-seq based transcriptome profiling of waterlogging response in cucumber hypocotyls reveals novel insights into the de novo adventitious root primordia initiation - Xu, Xuewen (BMC Plant Biol, 2017)
BACKGROUND: Waterlogging is a serious abiotic stress to plant growth because it results in the decline in the supplement of oxygen to submerged tissues. Although cucumber (Cucumis sativus L.) is sensitive to waterlogging, its ability to generate adventitious roots (ARs) facilitates gas diffusion and increases plant survival when the oxygen concentration is decreased. To gain a better understanding of the molecular mechanisms that enable de novo AR primordia emergence upon waterlogging, the RNA sequencing-based transcriptomic responses of two contrasting cucumber genotypes, Zaoer-N (waterlogging tolerant) and Pepino (waterlogging sensitive), which differed in their abilities to form AR were compared. RESULTS: More than 27,000 transcripts were detected in cucumber hypocotyls, from which 1494 and 1766 genes in ‘Zaoer-N’ and ‘Pepino’, respectively, were differentially expressed 2 days after waterlogging. The significant positive correlation between RNA sequencing data and a qPCR analysis indicated that the identified genes were credible. A comparative analysis revealed that genes functioning in carbohydrate mobilization, nitrate assimilation, hormone production and signaling pathways, transcription factors and cell division might contribute to the waterlogging-triggered AR primordia initiation. Ethylene was determined to be an important plant hormone responsible for the cucumber ARs initiation. Additionally, genes encoding cytochrome P450, ankyrin repeat-containing proteins and sulfite oxidases were determined as important in waterlogging acclimation. CONCLUSION: This research broadens our understanding of the mechanism underlying waterlogging-triggered ARs emergence, and provides valuable information for the breeding of cucumber with enhanced waterlogging tolerance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-017-1081-8) contains supplementary material, which is available to authorized users.